The challenge of networked enterprises for cloud computing interoperability - Mezgár, István; Rauschecker, Ursula (Computers in industry, 2014)
•Review the present status of international cloud standardization activities with the focus on interoperability.•A taxonomy of connecting virtual enterprise architectures and cloud environments has been introduced.•A cloud-based application for the manufacturing industry has been presented using it as an example of the previously presented taxonomy. Manufacturing enterprises have to organize themselves into effective system architectures forming different types of Networked Enterprises (NE) to match fast changing market demands. Cloud Computing (CC) is an important up to date computing concept for NE, as it offers significant financial and technical advantages beside high-level collaboration possibilities. As cloud computing is a new concept the solutions for handling interoperability, portability, security, privacy and standardization challenges have not been solved fully yet. The paper introduces the main characteristics of future Internet-based enterprises and the different CC models. An overview is given on interoperability and actual standardization issues in CC environments. A taxonomy on possible connecting forms of networked enterprises and cloud-based IT systems with reference on interoperability is introduced, parallel presenting four use cases as well. Finally, an example of connecting cloud and NE is presented as an effective application of cloud computing in manufacturing industry.